ANALYSIS OF HANDLING OF CATCH RESULTS ON THE QUALITY OF MACKEREL SCAD (Decapterus macarellus) USING ORGANOLEPTIC TECHNIQUES IN SIBOLGA MODERN FISH MARKET - Melda Anugrah Situmorang; Eddiwan Eddiwan; Mutiara Alkayakni Harahap; Kurniawan Fazri; Eka Saputra (Asian Journal of Aquatic Sciences, 2026)
Activities, including landing, processing, marketing, logistics, vessel and gear maintenance, and mooring. Organoleptic testing assesses fish quality based on sensory characteristics, including color, texture, odor, and the freshness of the eyes and gills. This test is conducted by panelists using a specific assessment scale. The objectives of this study were: 1) to analyze the handling process of mackerel after catching and until auction at the Sibolga Modern Fish Market; 2) to assess the quality of mackerel using organoleptic testing. A survey approach was used. A total of 66 people and one informant participated. The research results show that the blue scad (Decapterus macarellus) handling process begins with unloading, transport to the weighing area, weighing and recording, cooling after weighing, sorting before auction, auction at TPI, distribution after auction, and transportation to the market. Based on the organoleptic test sheet evaluation of 66 traders of blue scad (Decapterus macarellus), a comparison of fish quality categories was found in two obtaining areas. The quality of the fish declined throughout the afternoon and evening, with traders in the outer area (50) receiving a score sheet of 6 (quite fresh) and traders in the inner section (16) receiving a score sheet of 7 (fresh), indicating a decline in fish quality. The catch at PPN Sibolga was handled in accordance with KKP regulations, including sorting the fish by size and type, washing them with clean water, cooling them with ice, and offloading them swiftly and carefully